Size matching in lung transplantation: A narrative review - Tuba Apaydın; Ali Yeginsu (Archives of Organ Transplantation - Peertechz Publications, 2020)
Background: Size matching between donor lungs and recipient chest space is an important technical problem that affects the outcome and survival following lung transplantation. The size of the lung can vary according to underlying disease, previous resections, and ethnicity, as well as height, age, and sex. Measurements of predicted total lung capacity according to height, age, and sex are frequently used, although other measurement methods are available.  Result: Excessively large or small donor lungs are undesirable for lung transplantation because they cause complications. In general, post-transplant outcomes are better when the donor lung is reasonably larger than the recipient thoracic cavity. However, larger donor lungs are not recommended for recipients with emphysema. We performed a literature search using Medline/PubMed, the Cochrane Library Database, and Scielo to identify articles published between June 2016 and July 2018 related to the effect of lung size matching on the prognosis of lung transplant patients. The literature primarily provides information regarding double lung transplantation with a predicted total lung capacity for the donor of 75%-125% of the predicted recipient total lung capacity. Data are lacking with respect to the size mismatch for single lung transplantation and recipients with restrictive pulmonary disorders.  Conclusion: This review presents detailed findings regarding size matching in lung transplantation.